Visualized analysis of core themes and emerging frontiers in global chikungunya virus studies - Tian, Jing; Li, Yonggang; Zhao, Yuanlong; Tao, Xiaoli (Frontiers in Microbiology, 2026)
BackgroundChikungunya virus (CHIKV) is a mosquito-borne alphavirus that has caused multiple outbreaks worldwide in recent years, resulting in millions of infections and severe complications such as chronic arthritis, posing an ongoing threat to global public health.ObjectiveThis study employs bibliometric methods to systematically analyze the core themes, development trends, and research frontiers in CHIKV research, aiming to provide a scientific basis for research planning and prevention strategies.MethodsBased on the Web of Science Core Collection database, a total of 3,709 relevant publications from 2015 to 2024 were included. Visualization tools such as VOSviewer and CiteSpace were used to analyze countries/regions, institutions, authors, journals, keywords, and co-citation networks.ResultsThe results indicated that the United States, Brazil, and India were the most productive countries, while French institutions stood out in research output. Scott C. Weaver was identified as the most prolific author. Journals including PLOS Neglected Tropical Diseases, Viruses, and the Journal of Virology demonstrated significant influence in this field. Co-citation and keyword cluster analyses revealed that phylogenetic analysis, epidemiology, pathogenesis, drug therapy, and vaccine development represent current research hotspots. International collaboration plays a key role in promoting global phylogenetic studies and data integration.ConclusionsCHIKV research is expanding from epidemiology to pathogenic mechanisms, targeted therapies, and public health prevention strategies. Future efforts should focus on viral evolution mechanisms, host immune interactions, multi platform vaccine development, and the construction of global risk prediction models to address the persistent challenges posed by CHIKV outbreaks.